Developing academic literacy and voice: challenges faced by a mature esl student and her instructors (2010)
Drawing on critical, socio-cultural and sociolinguistic theories of writing, text and voice, this ethnographic study examines the challenges that a mature ESL student and her instructors in a university course on Spanish Language Media face as they co-construct a common understanding of academic literacy and voice in an undergraduate General Studies Program offered by a university in Western Massachusetts. Intertextual analysis of the data suggests that traditional product-based approaches to helping students develop academic literacy might not be very effective. However, to be able to take a different approach, such as the one suggested by genre scholars, both faculty teaching content subjects and writing tutors would need appropriate training. Key words: ESL writing, academic writing, academic voice, disciplinary writing Con base en teorías críticas, socioculturales y sociolingüísticas sobre escritura académica, texto y voz, este estudio etnográfico explora los retos que enfrentan una estudiante hablante de inglés como segunda lengua y sus profesores de un curso de Medios de Comunicación en Lengua Española al construir conjuntamente los conceptos de literacias académicas y de voz en un curso de pregrado en estudios generales ofrecido por una universidad en Massachusetts. El análisis intertextual de los datos recogidos muestra que algunos métodos tradicionales dirigidos a la elaboración de productos pueden resultar poco efectivos para apoyar el desarrollo de la escritura académica. Sin embargo, se concluye que para usar metodologías más efectivas, como las propuestas por las teorías de género, es indispensable que tanto los profesores de las diferentes materias como los tutores reciban el entrenamiento adecuado. Palabras clave: escritura de inglés como segunda lengua, escritura académica, voz académica, escritura disciplinaria